The Role of Civic Education in Promoting Diversity and Tolerance in Schools - Laros Tuhuteru; Abu Muna Almaududi Ausat; Emy Yunita Rahma Pratiwi; Suherlan Suherlan (Edumaspul: Jurnal Pendidikan, 2023)
In the era of globalisation, social diversity is increasingly becoming common in society. This diversity can manifest in various forms, such as differences in religion, ethnicity, race, and culture. This diversity is often a source of conflict and tension in society. Schools as one of the educational institutions are expected to contribute to creating a harmonious and peaceful society, where diversity is accepted and respected. This study aims to analyse the role of civic education in enhancing diversity and tolerance in schools. This research is qualitative in nature. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. This study shows the results that civic education has an important role in improving diversity and tolerance in schools. Through civic education, students can understand national values, rights and obligations as citizens, and develop an attitude of tolerance towards cultural, religious and ethnic differences.